Estudo comparativo entre estruturas de aço e estruturas mistas de aço e concreto aplicadas a edifícios de múltiplos andares - Oliveira, Letícia Cardoso de (2018)
This paper presents the design of steel structures and steel and concrete composite structures for a car park building and compares the obtained results, identifying advantages and disadvantages of the studied structural systems. The justification for this study is the demand for materials that help to chose a low cost structural system for a building. Three structures were designed: the first one is composed of steel columns, steel beams and composite slabs, while the second and third are composed of composite columns (concrete encased composite columns on the second and concret filled composite columns on the third) composite beams and composite slabs. The numerical model of the structure was carried out using the computer program SAP2000 and the design was made acordding to the Brazilian Standard ABNT NBR 8800:2008. Slenderness, steel consumption and the weight of the designed elements were evaluated. The results obtained for adopted structural systems show the best performance of the filled composite columns when compared to the encased composite columns and a reduction in steel consumption, but no reduction of the total weight of the structure, for the composite structures when compared to the steel structures. It is pertinent to use other structural systems in future studies.